Pemanfaatan Olahan Labu Kuning untuk MPASI sebagai Pencegahan Stunting pada Anak Balita - Adimas Ridhoni; Berta Dwi Rumekty; Candra Candra; Daniel Sapta Wijaya; Eric Timotius Hartono; Feby Cristina; Halimatul Sa’diah; Luthfia Ananda; Millenia Ardhia Garini; Reza Alviansyah; Shofura Febriyanti; Sri Yunita; Yosi Melani Kristinawati; Yudea Setiawan Peronika (FKIP, Universitas Palangka Raya, 2024)
Gunung Mas District, Central Kalimantan Province, has serious concerns about stunting, with prevalence remaining high at both national and local levels. Stunting, as an indication of chronic malnutrition, requires effective interventions to improve this condition. One strategic effort is through the provision of nutritious complementary foods, with pumpkin as a potential local ingredient. Previous studies have shown that pumpkin is high in nutrients and effective in improving the nutritional status of toddlers. Universitas Palangka Raya, through the UPR 2024 Regular KKN Period I team, conducted education in Belawan Mulia Village to increase the local people's knowledge and skills on pumpkin-based complementary feeding. Implementation methods included education to the local people's forum and village institutions, along with the provision of complementary foods. The program results showed that the use of brochures and stickers were effective in spreading the information. The program succeeded in increasing the local people's knowledge, changing their feeding behavior, and contributing to the reduction of stunting and improvement of children's nutritional status.